A C-Slotted Dual Band Textile Antenna for WBAN Applications - Ping, Jack Soh; Fatin Nabilah, Giman; Mohd Faizal, Jamlos; H., Lago; Azremi Abdullah, Al-Hadi (IEEE, 2016)
A dual band C-shaped slotted textile antenna with artificial magnetic conductor (AMC) is investigated in this paper. The proposed antenna is operates in the 2.45 GHz (lower) frequency band for WBAN applications and in the 5.8 GHz (upper) frequency band for WLAN applications. A diamond-shaped AMC is used to improve the antenna performance and reduce backwards radiation for on-body usage. The proposed antenna is fully fabricated using textiles and utilizes felt as its substrate and ShieldIt Super as its conducting elements. Simulations and comparison against a same antenna without the AMC plane indicated that this conformal antenna operates with good reflection coefficients, gains, and radiation pattern within the desired bands.